Differences in Romantic Relationship Experiences for Individuals with an Autism Spectrum Disorder. - Hancock, Grace; Stokes, Mark A.; Mesibov, Gary (Sexuality & Disability, 2020)
Individuals with an autism spectrum disorder (ASD) experience varying difficulties, for many this includes romantic relationships. Existing research in this area is mixed and suggests that compared to typically developing (TD) individuals, those with ASD have a similar level of romantic interest, but less relationship success and lower satisfaction with romantic connections. We aimed to explore one of the many pathways to positive relationship experience, and how these may differ for individuals with an ASD. We recruited 459 individuals (232 diagnosed with ASD) internationally, with 64% being female, a result of the internet-based sampling method. Each participant completed an online battery including the Sexual Behaviour Scale—third edition. Compared to TD individuals, those with ASD reported a similar level of interest in relationships, but reported fewer opportunities to meet potential new partners, had shorter relationship duration, and greater concern about their future relationships. Peer social engagement was found to partially mediate the relationship between diagnostic status and relationship difficulties. This was true for both males and females. Additionally, those with ASD reported learning less about sexuality from their peers and experiencing greater anxiety when meeting a potential partner. The current study identifies some factors and pathways that lead to positive relationship functioning among those with ASD. This will be useful for clinician's who support individuals on the autism spectrum, as it will assist those individuals seeking to establish or maintain positive romantic relationships.